MEDICATION ADHERENCE THROUGH DIGITAL HEALTH INTERVENTIONS: COMPREHENSIVE REVIEW - Maha Mohammed Al Jubran, Fatmah Maskor Koder Alanezy, Badriah Reda Alenezi, Aamal Shamat Alenazy, Souad Mohammed Alenazy, Albaqal Suaad Abdullah S, Khulood Mohammed Ali Alrefaie, ‏Nashmiah Fraih Abdullah Alshammari, ,; Fahad Humood Alenezi, Ali Mohamed Khormi, Mohammed Rabia Alanazi, Ali Mohammed Khdier Alenazi, Maryem Saud Khalaf Alrashedi, Woroud Jarallah Mualla Alreshidi, (Chelonian Research Foundation, 2022)
Electronic medication packaging (EMP) devices may enhance drug adherence, which is expected to impact patients with hypertension, hyperlipidemia, and diabetes. The objective is to examine the correlation between EMP devices and enhanced adherence, as well as to identify and define the typical characteristics of EMP devices. We did a comprehensive assessment of peer-reviewed publications that examined the efficacy of EMP systems. The articles were retrieved from the MEDLINE, EMBASE, PsycINFO, CINAHL, and International Pharmaceutical Abstracts databases. The searches were completed up to June 13, 2014. We identified the correlations between the treatments and adherence, along with other significant discoveries. We evaluated every research for bias by using the Cochrane Handbook for Systematic Reviews of Interventions. We conducted a comprehensive evaluation of the characteristics of EMP devices and therapies. We have found five prevalent features of EMPs: the ability to record dosage events and save a record of adherence, the use of audiovisual reminders to prompt dose, the presence of digital exhibits, continuous monitoring capabilities, and the provision of adherence performance feedback to patients. There are several types of EMP. Nevertheless, there is a scarcity of data supporting the effectiveness of EMP devices, and the studies conducted to test them have shown inconsistent quality. Furthermore, there is evidence of bias in the reporting of this research. Devices that are included into the care delivery system and specifically intended to record dosage events are often linked to enhanced adherence. More rigorous research is required to ascertain the impact, if any, of these cost-effective treatments on drug nonadherence and discover their most effective elements. Keywords: Electronic medication packaging (EMP), drug adherence, review, drug nonadherence, treatment.